Activation and Cellular Localization of the Cyclosporine A-sensitive Transcription Factor NF-AT in Skeletal Muscle Cells - Abbott, Karen L. (The American Society for Cell Biology, 1998)
The widely used immunosuppressant cyclosporine A (CSA) blocks nuclear translocation of the transcription factor, NF-AT (nuclear factor of activated T cells), preventing its activity. mRNA for several NF-AT isoforms has been shown to exist in cells outside of the immune system, suggesting a possible mechanism for side effects associated with CSA treatment. In this study, we demonstrate that CSA inhibits biochemical and morphological differentiation of skeletal muscle cells while having a minimal effect on proliferation. Furthermore, in vivo treatment with CSA inhibits muscle regeneration after induced trauma in mice. These results suggest a role for NF-AT–mediated transcription outside of the immune system. In subsequent experiments, we examined the activation and cellular localization of NF-AT in skeletal muscle cells in vitro. Known pharmacological inducers of NF-AT in lymphoid cells also stimulate transcription from an NF-AT–responsive reporter gene in muscle cells. Three isoforms of NF-AT (NF-ATp, c, and 4/x/c3) are present in the cytoplasm of muscle cells at all stages of myogenesis tested. However, each isoform undergoes calcium-induced nuclear translocation from the cytoplasm at specific stages of muscle differentiation, suggesting specificity among NF-AT isoforms in gene regulation. Strikingly, one isoform (NF-ATc) can preferentially translocate to a subset of nuclei within a single multinucleated myotube. These results demonstrate that skeletal muscle cells express functionally active NF-AT proteins and that the nuclear translocation of individual NF-AT isoforms, which is essential for the ability to coordinate gene expression, is influenced markedly by the differentiation state of the muscle cell.